Preserving cultural heritage through radiation-curing resin consolidation: a case study of an indigenous ceramic vessel - Ana Carolina Delgado Vieira; Pablo Antonio Vasquez Salvador; Maria José Alves de Oliveira; Fabiola Andrea da Silva (Brazilian Journal of Radiation Sciences)
This article presents a case study on a ceramic vessel belonging to the Amazonian indigenous people, Asurini do Xingu, to investigate the use of gamma radiation for consolidating cultural heritage. Traditionally, gamma radiation is used to impregnate cultural artifacts with a radiocurable resin. In this study, the consolidating resin was applied only to the external surface of the vessel by brushing. The object was weighed before and after consolidation, and a colorimeter was used to evaluate possible color changes. The results indicated that the method was effective, with no negative effects on the appearance of the cultural item.